Teachers' understanding of computational thinking unplugged implementation in the merdeka curriculum in the education services of Majalengka District - Nugroho, Eddy Prasetyo; Wahyudin, Asep; Anisyah , Ani; Fathimah, Nusuki Syari’ati; Nurkhofifah, Eva (Universitas Ahmad Dahlan, 2024)
This activity aims to provide an understanding to teachers who are engaged in seeking to enhance the competence of teachers in conducting merdeka curriculum, improving critical thinking skills, and problem-solving using Computational Thinking with unplugged learning. Computational Thinking becomes the learning needed in 21st century education in an independent curriculum and one of the skills that needs to be integrated into education. Teachers, as the main pillar of education, play an important role in the mastery of Computational Thinking in pupils. Based on discussions with some teachers at Majalengka, the teachers still do not understand the concept and application of Computational Thinking in learning. Computational Thinking can be taught and trained without using a computer commonly known as unplugged learning. This activity uses the Community-Based Participatory Research (CBPR) methodology in which Teachers and Students of the Computer Science Studies Program collaborate with the Majalengka District Education Service to contribute to providing service learning to teachers at all levels of education to implement Computational Thinking learning with unplugged learning in their respective schools. The results showed that 54.8% of teachers understood and mastered Computational Thinking with unplugged methods, 78.6% of the teachers considered unplugged methods important to support the learning process.